The Role of Vitamin D in Uterine Fibroid Biology - Brakta, Soumia (Fertil Steril, 2015)
OBJECTIVE: To provide a detailed summary of current scientific knowledge on uterine fibroids (leiomyomas) in vitro and in in vivo animal models, as well as to postulate the potential role of vitamin D3 as an effective, inexpensive, safe long-term treatment option for uterine fibroids. DESIGN: PubMed search articles were used to identify the most relevant studies on uterine fibroids as well as effects of vitamin D3 on uterine fibroid cells and fibroid tumor growth in in vivo animal models. SETTING: University research laboratory - affiliated infertility clinic. PATIENT(S): Not applicable. INTERVENTION(S): None MAIN OUTCOME MEASURE(S): Not applicable. RESULTS: Despite numerous publications available on uterine fibroids, information about the role that vitamin D3 plays in the regulation of uterine fibroids are limited. Most of the recent vitamin D3-related studies on uterine fibroids were published from our group. Recent studies have demonstrated that vitamin D deficiency plays a significant role in the development of uterine fibroids. Our recent studies have demonstrated that vitamin D3 reduces leiomyoma cell proliferation in vitro, and leiomyoma tumor growth in in vivo animal models. These results postulate the potential role of vitamin D3 for an effective, safe non-surgical medical treatment option for uterine fibroids. CONCLUSIONS: This article reviews human and animal studies and uncover new possibilities for understanding the vitamin D-based therapeutic option for an effective, safe long-term treatment of uterine fibroids. Based on these results, a clinical trial with vitamin D3 or a hypocalcemic analog, paricalcitol may be warranted for non-surgical medical treatment of uterine fibroids.